Primary production of Swartvlei in mid-summer 1980, with emphasis on the production ecology of the littoral zone - Taylor, David Ian (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1981)
From Introduction: Energy passes through an ecosystem via a multiplicity of interconnected routes, which can be broadly categorised into trophic and detrital pathways. The "metabolic activity" of most lakes will be governed predcminantly at the base of these two routes; namely, the primary producer and decanposer levels, respectively (Wetzel and Allen, 1972). The importance of the littoral primary producers (especially the aquatic macrophytes) in the functioning of the Swartvlei ecosystem has been emphasised in a comprehensive report by Howard-Williams and Allanson (1978) dealing with the lake system fran 1975 to 1978. They noted that although the littoral shelf (<2m below low water level) occupies only 43% of the lake's surface area it contributed 64% of the total annual primary production during the period investigated. This was largely due to the dense Potamogeton pectinatus stands which alone accounted for 52% of the total carbon input into the lake by plants. The fact that the production/biomass ratio for P. pectinatus was only 1,2:1 suggested that its importance as a primary producer in Swartvlei was largely due to its high bianass. (Biomass, or standing stock, is used in this report as defined by Waters (1977); namely, "the amount present at a point in time, expressed best as quantity per spatial unit".)
Keywords: Estuarine ecology -- South Africa; Estuarine ecology -- South Africa -- Swartvlei; Ecology -- Research -- South Africa